Timing and intensity of light correlate with body weight in adults. - Kathryn J Reid; Giovanni Santostasi; Kelly G Baron; John Wilson; Joseph Kang; Phyllis C Zee (PLoS ONE)
Light exposure can influence sleep and circadian timing, both of which have been shown to influence weight regulation. The goal of this study was to evaluate the relationship between ambient light, sleep and body mass index. Participants included 54 individuals (26 males, mean age 30.6, SD = 11.7 years). Light levels, sleep midpoint and duration were measured with wrist actigraphy (Actiwatch-L) for 7 days. BMI was derived from self-reported height and weight. Caloric intake was determined from 7 days of food logs. For each participant, light and activity data were output in 2 minute epochs, smoothed using a 5 point (10 minute) moving average and then aggregated over 24 hours. The mean light timing above 500 lux (MLiT500) was defined as the average clock time of all aggregated data points above 500 lux. MLiT500 was positively correlated with BMI (r = 0.51, p<0.001), and midpoint of sleep (r = 0.47, p<0.01). In a multivariable linear regression model including MLiT500 and midpoint of sleep, MLiT500 was a significant predictor of BMI (B = 1.26 SE = 0.34, β = 0.53 p = 0.001, r2Δ = 0.22). Adjusting for covariates, MLiT500 remained an independent predictor of BMI (B = 1.28 SE = 0.36, β = 0.54, p = 0.002, r2Δ = 0.20). The full model accounted for 34.7% of the variance in BMI (p = 0.01). Exposure to moderate levels of light at biologically appropriate times can influence weight, independent of sleep timing and duration.